Perencanaan Instalasi Penangkal Petir Pada Bangunan Industri Bengkel Pembuatan Mesin CV. Karya Brawijaya - Rohmanita Duanaputri; Ruwah Joto; Sigi Syah Wibowo; Fery Nova Dwi Prasetyo (Elposys: Jurnal Sistem Kelistrikan, 2021)
In this era, Indonesia's industry is rapidly developing and relies heavily on electrical components, especially in the Agro-Industry Machine Workshop of CV. Karya Brawijaya. CV. Karya Brawijaya is an industry that produces agro-industrial machinery. In the planning of external protection systems, the commonly used methods are conventional lightning rods and electrostatic methods. Therefore, to further examine the situation, observations conducted in the industry revealed the absence of a lightning protection system. Hence, the author aims to plan and compare the two types of lightning protection systems, namely conventional (Franklin) and electrostatic (E.F. Lightning Protection System), in terms of protection, technical aspects, economy, advantages, and disadvantages. The research and observations were conducted in the CV. Karya Brawijaya building area, using data collection techniques such as direct observation, interviews, and literature studies. This process yielded building layout data (height, width, and length) and data on thunderstorm days in 2019 (IKL 243). These data were then used to calculate the parameters for lightning protection system installation planning according to the standards set by SNI 07015-2004 and PUIPP. The results of the conventional method (Franklin) planning, with air terminations using rolling spheres, showed that 9 finials were installed, allowing the building to withstand currents up to 160.06 kA. On the other hand, the electrostatic method (E.F. Lightning Protection System) planning resulted in the installation of 1 finial, enabling the building to withstand currents up to 23.737 kA. If the current exceeds these values, the lightning protection system will capture the lightning strike.